"Carne sem osso e farinha sem caroço": o motim de 1858 contra a carestia da Bahia - Reis, João José; Aguiar, Márcia Gabriela D. de (Revista de História, 1996)
This article is a study of a food riot in Bahia in 1858. The authors describe the events, discuss the profile of the protestors, analyze the movement as a defense of the"moral economy" and emphasize its political magnitude.